Generation of power: economic, social and environmental - Magnuson, John (My University, 2008)
Paper written by John Magnuson in the fall semester 2008 at the University of Wisconsin-River Falls for Dr. Greta Gaard's English 228 class. In this paper, the author discusses how the generation of energy by hydroelectric dams, nuclear power plants and oil refineries results in changes to the sociological, ecological and economic interactions between humans, animals and the environment.
6 p.
Keywords: Nuclear energy--Social aspects; Environmental justice; Oil refineries; Petroleum refineries--Environmental aspects; Nuclear power; Nuclear power plants; Hydroelectric power plants--Social aspects; Nuclear energy--Economic aspects; Hydroelectric power plants--Economic aspects; Petroleum refineries--Economic aspects; Nuclear energy--Environmental aspects; Petroleum refineries--Social aspects; Hydroelectric power; Hydroelectric power plants--Environmental aspects; Hydroelectric dams